Asuhan Kebidanan Pada Bayi Baru Lahir dengan Perawatan Tali Pusat Di Klinik Pratama Medical Center Kota Batam - Sthepani Sari Hidayat; Susanti Susanti (Pusat riset dan Inovasi Nasional, 2024)
Newborns also called neonates are individuals who are growing and have just experienced birth trauma and must be able to make adjustments from intra uterine life to extra uterine life. A normal newborn is a baby born at 37-42 weeks gestation and weighs 2,500-4,000 grams. Care taken of newborns is care of hair, eyes, nose, mouth, ears and one of them is umbilical cord care. Umbilical cord care is needed to prevent the umbilical cord from becoming a breeding medium for pathogenic microorganisms: Incorrect care techniques can lead to tetanus neonatorum infection which can affect the length of cord detachment. This type of research is descriptive by applying a case study approach. The implementation of this study was carried out at the Pratama Medical Center Clinic on Mrs. W's baby by providing umbilical cord care to her baby.